Ruptured Cesarean Scar Pregnancy: A Case Report - Johanes Nyoman Deo Widiswara Mawan; I Nyoman Hariyasa Sanjaya; Tjokorda Gde Agung Suwardewa; Ida Bagus Gede Fajar Manuaba (International Journal of Social Service and Research, 2023)
Ectopic pregnancy is defined as implantation outside the uterine cavity with an incidence rate of 19 per 1000 conceptions in the United States, accounting for >64,400 hospitalizations annually. It is the leading cause of maternal death in the first trimester. Most ectopic pregnancies (98%) occur in the fallopian tube but can also occur elsewhere. Cesarean scar pregnancy is a form of ectopic implantation in the fibrous tissue around the scar of previous cesarean delivery. The first case of cesarean scar pregnancy was described by Larsen and Solomon in 1978, and only 19 cases were reported until 2001. 3 The incidence of cesarean scar pregnancy is estimated to be 1:1800 to 1:2216 pregnancies. This condition represents 6.1% of all ectopic pregnancies with a history of at least one cesarean operation. In Indonesia, this case is rarely reported, and there is no data on the prevalence of this disease in Indonesia. Due to its rarity, we report a case of a 37-year-old G2P0100 woman with ruptured cesarean scar pregnancy.